Topics in Acoustic Echo and Noise Control Selected Methods for the Cancellation of Acoustical Echoes, the Reduction of Background Noise, and Speech Processing - Hänsler, Eberhard; Schmidt, Gerhard (Signals and Communication Technology, 2006)
In this book, an international team of highly qualified experts treats important topics in acoustic echo and noise control and reports the latest developments. Methods for enhancing the quality of speech signals are gaining growing attention in universities and in industrial development laboratories. This book is organized in five parts: Part I gives a short introduction to acoustic echo and noise control. Part II deals with multi-microphone processing. In Part III, advanced methods for both linear and nonlinear echo cancellation are presented, and techniques for intelligent control of hands-free telephones are introduced. Part IV is devoted to noise reduction procedures. An in-depth treatment of conventional and of advanced methods is given, followed by a model based approach using Kalman filters. Finally, in Part V, selected applications of acoustic echo and noise control as well as speech and audio processing in general are outlined. Topics such as auditory scene analysis, wave field synthesis for spatial sound reproduction, in-car communication systems, and hearing aids are treated.